The Role Of Quality In Customers` Satisfaction With The Provided Banking Services (A Field Study On The Customers Of The Commercial Bank Of Syria In The Governorate Of Lattakia, Using The Gap Models) - حمدان مهند (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Ñ  ABSTRACT Ñ This research has aimed to identify the level of quality of banking services provided in the branches of the bank under study, to know the relative importance of the main and subsidiary dimensions of the quality of banking service, and to study the relationship between quality and customer satisfaction. The study relied on the approach of the gap theory, to compare the actual performance of the service provided and the expected performance Of them, the research sample consisted of (314) sample from commercial bank branch clients in Lattakia Governorate. The most important results of the research were as follows: It was found that there are significant differences between the dimensions of perceived and expected quality and at the level of all the main dimensions, and these differences were in favor of the expected quality dimensions, meaning that the quality of banking service meets part of customer expectations, and according to the scale of gaps, the most satisfactory dimensions to customers are: the tangible elements, followed by security Then sympathy, as for the least customer satisfaction, which is reliability and response, and there is a significant relationship between quality and customer satisfaction.